Image diagnosis of Trigeminal Neuralgia caused by Vascular Compression - Haque, Moududul; Islam, AKM Tarikul; Rahman, Asifur; Mukharjee, Sudipta Kumar; Hossain, ATM Mosharef (Bangladesh Journal of Neurosurgery, 2020)
Trigeminal Neuralgia (TGN) is a disease frequently encountered by the neurologists and neurosurgeons. The typical pain of TGN is lancinating in nature in one side of face along the distribution of Trigeminal nerve. Pain is sharp shooting and periodic in nature, aggravated by various factors, like eating, talking, laughing. A typical trigeminal neuralgia is caused by compression to the Root exit zone (REZ) by superior cerebellar artery (SCA), aberrant loop of Antero inferior cerebellar artery (AICA), dolichobasilar artery or a large sized vein. However facial pain mimicking TGN may occur by a tumor, plaque of Multiple sclerosis or may be idiopathic. So this is very important to know the cause of TGN/ facial pain for planning of specific treatment. Most of the patients remain pain free by medical management by using Carbamazepine, oxycarbazepine, Pregabalin, Gabapentin, Clonazepam etc. But medically refractory TGN can be treated by Microvascular decompression (MVD) with significantly satisfactory results if the cause is by vascular compression. However during MVD no significant blood vessels are seen and surgery become failed. Clinical examination and evaluation is very important, however to become confirmed about the pathogenesis needs imaging of brain. MRI of brain can differentiate any tumor or Plaque of MS. But conventional MRI images can not show us clearly the blood vessel causing TGN. Conventional MRA could show the blood vessels, which might be causing compression to REZ but does not confirm the fact. Constructive interference in steady state (CISS) MR images were evaluated in our 15 cases to find neurovascular relationship at the REZ. In 11 cases CISS images showed excellent visualization of fifth nerve and blood vessels causing compression to REZ in all case of TGN who underwent Microvascular decompression (MVD) with excellent result. In 2 patients we depended on clinical findings and T2 MR Images. In one of them we could find Offending vessels who were also improved clinically. In one case we did not find any significant offending vessel except a small vein and this patient did not show any improvement. In rest two cases, in one patient CISS showed a tiny vessel and after MVD the patient did not improve. In one patient no significant vessels were not seen in CISS images. We did not go for MVD for this case. So the pre-operative CISS MR images are more precise to show the neurovascular relationship and determine the offending blood vessel causing TGN. Thus we can avoid an unnecessary MVD. Bang. J Neurosurgery 2020; 10(1): 3-8